2022
DOI: 10.1161/atvbaha.121.317204
|View full text |Cite|
|
Sign up to set email alerts
|

Macrophage ALDH2 (Aldehyde Dehydrogenase 2) Stabilizing Rac2 Is Required for Efferocytosis Internalization and Reduction of Atherosclerosis Development

Abstract: BACKGROUND: Clinical studies show that the most common single-point mutation in humans, ALDH2 (aldehyde dehydrogenase 2) rs671 mutation, is a risk factor for the development and poor prognosis of atherosclerotic cardiovascular diseases, but the underlying mechanism remains unclear. Apoptotic cells are phagocytosed and eliminated by macrophage efferocytosis during atherosclerosis, and enhancement of arterial macrophage efferocytosis reduces atherosclerosis development. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…24 Additionally, estrogen has an inhibitory effect on diet-induced atherosclerosis formation. [25][26][27] Therefore, to accelerate lesion formation, only male animals were used in our study. To establish atherosclerotic lesions, 6-to 8-week-old male ApoE −/− , ApoE −/− NEAT1 −/− , and ApoE −/− METTL14 +/− mice were fed a high-fat diet (HFD) containing 10% lard, 4% milk powder, 2% cholesterol, and 0.5% sodium cholate for 12 weeks.…”
Section: Animalsmentioning
confidence: 99%
“…24 Additionally, estrogen has an inhibitory effect on diet-induced atherosclerosis formation. [25][26][27] Therefore, to accelerate lesion formation, only male animals were used in our study. To establish atherosclerotic lesions, 6-to 8-week-old male ApoE −/− , ApoE −/− NEAT1 −/− , and ApoE −/− METTL14 +/− mice were fed a high-fat diet (HFD) containing 10% lard, 4% milk powder, 2% cholesterol, and 0.5% sodium cholate for 12 weeks.…”
Section: Animalsmentioning
confidence: 99%
“…However, inactivating mutations in ALDH2 (called ALDH2*2 or rs671 mutants) are risk factors for the development and poor prognosis of atherosclerotic cardiovascular disease. By using RNA-seq, proteomics, and immunoprecipitation experiments, we later discovered and verified Rac2 as its downstream target, demonstrating the crucial function of the ALDH2-Rac2 axis in mediating cytokinesis during atherosclerosis ( 170 ). As a result, many genes are present in the body as a “double-edged sword,” and even in diseases that are linked to specific mutations, they can have opposing effects.…”
Section: Current Shortcomings and Future Prospectsmentioning
confidence: 93%
“…Possibly, detailed knowledge on ALDH2 downstream targets might positively alter this gloomy outlook. Nevertheless, Zhang et al 17 have elegantly elucidated yet another piece of the complicated biological puzzle of dead cell removal in atherosclerosis.…”
Section: See Accompanying Article On Page 700mentioning
confidence: 99%
“…18 The role of RAC1-dependent actin dynamics has been studied before in foam cell macrophages, yet it was unknown if and how RAC2 was involved. Zhang et al 17 now show that ALDH2 protects RAC2 from ubiquitin-mediated degradation and hence improves efferocytosis. With loss- and gain-of-function experiments, the authors confirmed that the ALDH2-RAC2 axis was crucial for efferocytosis.…”
mentioning
confidence: 92%
See 1 more Smart Citation